Podobny w inności i inny w podobieństwie – rzecz o spotkaniu innego w ujęciu Józefa Tischnera - Mizdrak, Inga (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2014)
Otherness is encountered, noticed and, as the case may be, analyzed in a relation, because it is in a relation that the identity of I and the identity of You is revealed, and our identity is basically rooted in the individual constitution of a specific I and a specific You. The aim of the present study is to probe the phenomenon of otherness (alterity), and through it the fundamental question of who is the other we encounter, and next to show the main ways of experiencing the encounter with the other, which always occurs in the sphere of good and evil. In Józef Tischner’s view the experience of the other is a fundamental one, in that it reveals much of our own self-experience. My encounter with the other also throws into relief myself as the other and the fact that his otherness is different from mine. In the beginning of this discovery of otherness, the gap between I and You appears to be unbridgeable. But Tischner believes that the sensation of separateness and even of “being alien” assumes a kind of similarity, with the proviso that the latter occurs on the plane of our mutual being for each other. Tischner stresses otherness in similarity and similarity in otherness, both constituted and coexistent in the relation between I and You. Tischner’s idea involves a paradox: to open oneself to the alterity of the other, we have in a way to “bear” our own otherness and thereby to come to be “for the other”.